Differential protein–protein interactions of LRRK1 and LRRK2 indicate roles in distinct cellular signaling pathways. (14th July 2014) - Reyniers, Lauran; Del Giudice, Maria Grazia; Civiero, Laura; Belluzzi, Elisa; Lobbestael, Evy; Beilina, Alexandra; Arrigoni, Giorgio; Derua, Rita; Waelkens, Etienne; Li, Yan; Crosio, Claudia; Iaccarino, Ciro; et al.
Abstract Genetic studies show that LRRK2, and not its closest paralogue LRRK1, is linked to Parkinson's disease. To gain insight into the molecular and cellular basis of this discrepancy, we searched for LRRK1‐ and LRRK2‐specific cellular processes by identifying their distinct interacting proteins. A protein microarray‐based interaction screen was performed with recombinant 3xFlag‐LRRK1 and 3xFlag‐LRRK2 and, in parallel, co‐immunoprecipitation followed by mass spectrometry was performed from SH‐SY5Y neuroblastoma cell lines stably expressing 3xFlag‐LRRK1 or 3xFlag‐LRRK2. We identified a set of LRRK1‐ and LRRK2‐specific as well as common interactors. One of our most prominent findings was that both screens pointed to epidermal growth factor receptor (EGF‐R) as a LRRK1‐specific interactor, while 14‐3‐3 proteins were LRRK2‐specific. This is consistent with phosphosite mapping of LRRK1, revealing phosphosites outside of 14‐3‐3 consensus binding motifs. To assess the functional relevance of these interactions, SH‐SY5Y‐LRRK1 and ‐LRRK2 cell lines were treated with LRRK2 kinase inhibitors that disrupt 14‐3‐3 binding, or with EGF, an EGF‐R agonist. Redistribution of LRRK2, not LRRK1, from diffuse cytoplasmic to filamentous aggregates was observed after inhibitor treatment. Similarly, EGF induced translocation of LRRK1, but not of LRRK2, to endosomes. Our study confirms that LRRK1 and LRRK2 can carry out distinct functions by interacting with different cellular proteins. <boxed-text content-type="graphic" id="jnc12798-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> LRRK1 and LRRK2 (leucine‐rich repeat kinase) interaction partners were identified by two different protein‐protein interaction screens. These confirmed epidermal growth factor receptor (EGR‐R) as a LRRK1‐specific interactor, while 14‐3‐3 proteins were LRRK2‐specific. Functional analysis of these interactions and the pathways they mediate shows that LRRK1 and LRRK2 signaling do not intersect, reflective of the differential role of both LRRKs in Parkinson's disease.